The Potential Legal Issues, and Challenges of Utilising Geoengineering in Climate Change Mitigation - Mukhlish, Mukhlish; Aidonojie, Paul Atagamen; Jufri, Muwaffiq; Mustafa , Mundu M.; Aidonojie, Esther Chetachukwu (Prophetic Law Review, 2026)
Geoengineering is considered a potential scientific technique involving carbon dioxide removal and solar radiation management, aimed at manipulating Earth's climate to mitigate the effects of global climate change. However, despite the potential of geoengineering, there are several legal, environmental, socio-economic, and ethical issues associated with its reliance. Concerning this, the aim is to evaluate geoengineering as an option for mitigating climate change while critiquing legal deficiencies and proposing policy measures for its regulation. Hence, the study adopts a doctrinal method, relying on primary and secondary research materials such as international law, scholarly articles by learned authors, and other relevant sources. A descriptive and analytical style was adopted in analysing the data obtained from the research sources. The findings reveal that the scientific concept of geoengineering is quite promising in mitigating the impacts of climate change through carbon emissions and the management of solar radiation. However, there seems to be a lack of clear legal regulation, leading to a lack of oversight of geoengineering activities, uncertainty about liability for environmental harm, and cross-border issues. Furthermore, developing countries may also face the challenges of adapting to new scientific concepts, given the technical and scientific skills involved, and the inability to fund the geoengineering project. The study agrees that geoengineering has the potential to curtail climate change but concludes that its legal, ethical, and socio-economic challenges should be addressed by the international community through an effective legal framework and the provision of financial aid to developing countries to ensure the responsible application of geoengineering in climate change mitigation.